Viral Disease and Lipid Peroxidation in Conditions of Biotic and Abiotic Stress of Sambucus nigra L. Plants - Taran, Oksana; Mishchenko, Lidya; Nesterova, Nataliia; Dunich, Alina (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
For the first time in Ukraine, a virus disease of elderberry (Sambucus nigra L.) was found. Plants with symptoms of a viral infection were found in 2015–2016 in the Poltava region, in 2016 the same symptoms on elder plants were disfigured in the Kiev region. The symptoms of the disease and the morphological properties of the virus were studied. We found plants with chlorotic symptoms, mosaic and chain mail, plants rolling on the tops of leaves, and twisting the edges. In the leaves of infected plants, filamentous virions with a particle length of 650 }50 nm were detected by the method of electron microscopy. Based on the scientific literature data, viruses that can infect elder plants in Ukraine are screened. The levels of lipid peroxidation in older plants under conditions of viral infection and heat stress were studied. It is shown that a viral infection significantly reduces the content of TBA-active products in elder plants. The content of malonic dialdehyde significantly increased under conditions of heat stress in plants with symptoms of viral infection. At the same time, the content of TBA-active products in the leaves of healthy plants was insignificant. This indicates a negative effect of viral infection on the antioxidant system of elder plants. Further studies are needed to establish the systematic position of the detected viral particles and to create diagnosticums for the detection of these viruses. It is also necessary to study the ecological links of viruses identified in elderberry.